Enhanced Suppressive Activity of Regulatory T Cells in the Microenvironment of Malignant Pleural Effusions - Joanna Budna; Mariusz Kaczmarek; Agata Kolecka-Bednarczyk; Łukasz Spychalski; Piotr Zawierucha; Joanna Goździk-Spychalska; Michał Nowicki; Halina Batura-Gabryel; Jan Sikora (Journal of Immunology Research)
Cancer metastatic spread to serous cavity causes malignant pleural effusions (MPEs), indicating dismal prognosis. Tumor microenvironment can implement suppressive activity on host immune responses. Thus, we investigated the prevalence of Tregs and the relationship between them and TGF-β and IL-10 concentrations and measured expression of FOXP3, CTLA-4, CD28, and GITR genes, as well as protein expression of selected genes in benign effusions and MPEs. The percentage of Tregs was determined by means of multicolor flow cytometry system. TGF-β and IL-10 concentrations were measured using human TGF-β1 and IL-10 ELISA kit. Relative mRNA expression of studied genes was analyzed by real-time PCR. The frequency of Tregs was significantly higher in MPEs compared to benign effusions; however, the level of TGF-β and IL-10 in analyzed groups was comparable, and no correlation between concentrations of TGF-β and IL-10 and percentage of Tregs was observed. Relative mRNA expression of all the genes was higher in CD4+CD25+ compared to CD4+CD25− cells. In CD4+CD25+ cells from MPEs, relative mRNA expression of FOXP3, CTLA-4, and CD28 genes was significantly higher than in benign effusions; however, the level of CD4+CD25+CTLA-4+ cells in analyzed groups showed no significant differences. We found numerous genes correlations in an entire CD4+CD25+ cell subset and CD4+CD25+ cells from MPEs. Enhanced suppressive activity of Tregs is observed in the microenvironment of MPEs. Understanding of relations between cellular and cytokine immunosuppressive factors in tumor microenvironment may determine success of anticancer response.